2012
DOI: 10.1007/s10549-012-2101-x
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 gene amplification by fluorescence in situ hybridization (FISH) compared with immunohistochemistry (IHC) in breast cancer: a study of 528 equivocal cases

Abstract: The concordance rate between fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) on evaluating HER-2/neu status is still controversial, especially for the IHC 2+/equivocal cases. In this study, we investigated the amplification of HER-2/neu gene by FISH in IHC (2+)/equivocal specimens to clarify the correlation between HER-2/neu and clinicopathologic features of breast cancers. HER-2/neu amplification was determined by FISH on 528 specimens of breast carcinomas with equivocal expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
14
2
Order By: Relevance
“…Gene amplification could be demonstrated only in some of the samples that are found 2+ by IHC (Yeh). Studies have reported that FISH positivity in IHC 2+ samples varies between 7% and 89% (Ciampa et al, 2006;Rossi et al, 2006;Kuo et al, 2007;Sui et al, 2009;Goud et al, 2012;Zhang et al, 2012). Such diverse results might be due to the differences in the number of patients included in studies, centers' and/or pathologists' experience, and the test kits used.…”
Section: Discussionmentioning
confidence: 99%
“…Gene amplification could be demonstrated only in some of the samples that are found 2+ by IHC (Yeh). Studies have reported that FISH positivity in IHC 2+ samples varies between 7% and 89% (Ciampa et al, 2006;Rossi et al, 2006;Kuo et al, 2007;Sui et al, 2009;Goud et al, 2012;Zhang et al, 2012). Such diverse results might be due to the differences in the number of patients included in studies, centers' and/or pathologists' experience, and the test kits used.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the incidence of amplification in IHC (++) cases have been reported as 6-25% (10,11). ASCO / CAP stated this rate as 23.9% (8).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cells, it was poven that oncoprotein Her-2 was able to promote proliferative, metastatic, and prosurvival events and correlated with a poor prognosis [9,22]. Furthermore, Her-2 expression induced a resistance to chemoradiotherapy, and its inhibition by a speci�ic monoclonal antibody, trastuzumab, yields the predominant clinical activity either alone or in combination with chemotherapy in the Her-2-positive breast cancers [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins implicated in this dysregulation, Her-2 functions as a pivotal role in breast cancer cells [9][10][11]. Her-2 oncogene induces the expression of a transmembrane receptor protein structurally similar to epidermal growth factor receptor (EGFR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation